JOQARÍ KLASSLARDA KÓRKEMLEW QURALLARÍN OQÍTÍWDA INFORMACIYALÍQ TÁLIM PLATFORMALARÍNAN PAYDALANÍW - Jiemuratova, A.S. (SCIENCE and SOCIETY, 2024)
This article provides information about the use of modern information technologies in the teaching of the Karakalpak language, and interactive activities on educational platforms in teaching the methods of transferring meaning.